GRAMMATICAL CATEGORIES OF THE UKRAINIAN LANGUAGE: COGNITIVE ASPECT - Barchuk, Volodymyr (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
Aim. Modern linguistics is developing new directions and aspects of research, in particular those that take into account the achievements of various scientific paradigms. Cognitive linguistics, which has been actively developing recently, is based primarily on the study of the lexical-semantic structure of cognitive units as cognitive concepts. However, the basis of basic cognitive categories are grammatical categories, which form and determine the key ideas of the mental representation of the world. In the proposed article, we aim to present the conditioning of worldview cognitive categories by grammatical categories, in particular the verb, which defines such concepts in the language picture as time, causality, and completeness (realization). Methods. The main research method is descriptive. The work also uses the method of comparative typological analysis of linguistic categories of different languages. The method of structural-semantic analysis is used when characterizing the thesaurus meaning of lexemes. The study of the categorical system of the verb and varieties of temporal semantics was carried out using the methodology of typological analysis. Results. It has been established that the grammatical category of temporality at the level of components (interval, tense, taxis) is unevenly represented by the sphere of cognitive categories. It has been determined that the category of morphological time (tense) dominates in the worldview picture of the world, which generally covers the idea of ​​time despite the fact that tense does not genetically determine the meaning of continuality, which is based on the primary idea of ​​duration as a change expressed by an interval. This is due to the fact that with the formation of modern civilization, a three-component structure of time perception (past, present, future) was formed with the dominance of the future, in the fabric of which there is a category of causal dependence of events (conditionality) of reality within successive time intervals. The idea of ​​the world and time is based on the need for activity for the sake of an unreal future. Practical significance. The results of the study provide material for clarifying or forming cognitive categories as derivatives of the most general and primary grammatical categories. The aspect of considering and interpreting categories that determine the linguistic picture of the world provides a comprehensive approach to solving linguocognitive problems, forming a holistic interparadigmatic theory of linguistic categories.